Tindak Tutur Ekspresif dalam Pidato Prabowo Subianto pada Puncak Hari Guru Nasional 2024 - Kartika Kartika; Asnawi Asnawi; Dita Puspita Junaedi; Dian Nurul Fitra (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to describe the types of expressive speech acts used by Prabowo Subianto in his speech at the 2024 National Teachers' Day commemoration. The research employs a qualitative approach with a pragmatic discourse analysis method. The data were obtained from the transcript of Prabowo Subianto speech and analyzed based on Searle’s theory of expressive speech acts. The results show that Prabowo used various forms of emotional expression, such as expressions of gratitude, praise, appreciation, hope, and social criticism. These expressive speech acts reflect the speaker’s attitudes and feelings toward teachers and the condition of education in Indonesia. In addition, the use of expressive speech acts in the speech illustrates the strategic role of language in building emotional closeness between the speaker and the audience, as well as in delivering political and social messages persuasively. These findings indicate that expressive speech acts are essential elements in effective political communication.